Agency Characteristics and the Use of Executive Orders. Issue 1 (2nd January 2018) - Kennedy, Joshua
ABSTRACT: Past scholarship has offered varying explanations for why presidents choose to use executive orders. However, to this point, much of what we know of unilateral powers does not adequately address the role the bureaucracy plays in the president's decision. This research seeks to account for bureaucratic factors as a strategic presidential consideration in the employment of such directives. I classify executive orders from 1989–2012 based on which agency or agencies they apply to, and consider the importance of various characteristics (e.g. agency ideology, level of centralization, politicization, etc.) in determining which organs of the bureaucracy presidents will direct executive orders to generally. The results provide evidence that the White House directs fewer executive orders to agencies that have a politically independent leadership structure, and this result holds across a variety of measures judging an order's impact. The results demonstrate that the type of directive is crucial in determining a president's strategic decision to use executive orders, in line with previous research, and that agency centralization is one crucial component of this strategic calculation.